2016
DOI: 10.1038/srep37955
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia and Pseudomonas aeruginosa acidify cystic fibrosis airway surface liquid by elevating epithelial monocarboxylate transporter 2 dependent lactate-H+ secretion

Abstract: The cystic fibrosis (CF) airway surface liquid (ASL) provides a nutrient rich environment for bacterial growth including elevated glucose, which together with defective bacterial killing due to aberrant HCO3− transport and acidic ASL, make the CF airways susceptible to colonisation by respiratory pathogens such as Pseudomonas aeruginosa. Approximately half of adults with CF have CF related diabetes (CFRD) and this is associated with increased respiratory decline. CF ASL contains elevated lactate concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 29 publications
3
54
2
Order By: Relevance
“…In addition, while this work was in progress, and in agreement with our results, Garnett et al [63] found that primary human bronchial epithelial cells (HBE) secrete lactate into the ASL;…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, while this work was in progress, and in agreement with our results, Garnett et al [63] found that primary human bronchial epithelial cells (HBE) secrete lactate into the ASL;…”
Section: Discussionsupporting
confidence: 90%
“…In our results became clear that cells with impaired CFTR activity (IB3-1 and Caco-2/pRS26 cells) reduce the pHe mainly due to differences in lactic acid production. On the other hand, one very important observation of Garnett et al [63] was that changes in the ASL pH were observed only under hyperglycemia or in the presence of P.…”
Section: Discussionmentioning
confidence: 98%
“…Efflux pumps are common across Gram-negative bacteria 54 , and their loss may be a general adaptive strategy for species that face similar pressures as N. gonorrhoeae and urogenitally-adapted N. meningitidis . In support of this, clinical isolates of Pseudomonas aeruginosa with truncations in genes homologous to mtrC 55, 56 and antibiotic hypersensitivity have been obtained from cystic fibrosis patients, in whom the thick mucus in airway environments can exhibit increased acidity and decreased oxygen availability 57, 58 .…”
Section: Discussionmentioning
confidence: 97%
“…Human primary epithelial cell cultures and cell lines have previously been established from other airway locations, including the posterior commissure, trachea, and small airways of the lung . These are, however, unlikely to reflect the subglottic region.…”
Section: Discussionmentioning
confidence: 99%